2015
DOI: 10.3791/52908
|View full text |Cite
|
Sign up to set email alerts
|

Induction and Assessment of Ischemia-reperfusion Injury in Langendorff-perfused Rat Hearts

Abstract: The biochemical events surrounding ischemia reperfusion injury in the acute setting are of great importance to furthering novel treatment options for myocardial infarction and cardiac complications of thoracic surgery. The ability of certain drugs to precondition the myocardium against ischemia reperfusion injury has led to multiple clinical trials, with little success. The isolated heart model allows acute observation of the functional effects of ischemia reperfusion injury in real time, including the effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 17 publications
0
27
0
1
Order By: Relevance
“…Because it is deprived of neural and humoural regulation. 35 Therefore, the regulatory role of GAS5 on myocardial I/R injury should be further confirmed in vivo. On the other hand, although we found that GAS5 knockdown protected against myocardial I/R injury, meanwhile it repressed ROCK1 and activated PI3K/AKT, whether activation of ROCK1 or inhibition of PI3K/AKT by genetic or pharmaceutical methods rescued the cardioprotection of GAS5 knockdown is still not confirmed.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Because it is deprived of neural and humoural regulation. 35 Therefore, the regulatory role of GAS5 on myocardial I/R injury should be further confirmed in vivo. On the other hand, although we found that GAS5 knockdown protected against myocardial I/R injury, meanwhile it repressed ROCK1 and activated PI3K/AKT, whether activation of ROCK1 or inhibition of PI3K/AKT by genetic or pharmaceutical methods rescued the cardioprotection of GAS5 knockdown is still not confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…The hearts in this model could not perfectly mimic the pathophysiological process of myocardial IR injury. Because it is deprived of neural and humoural regulation . Therefore, the regulatory role of GAS5 on myocardial I/R injury should be further confirmed in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Today, the Langendorff heart assay is a predominant technique in vitro, which is used in physiological and pharmacological research. It allows the examination of cardiac contractile strength and heart rate without complications of an intact animal (Herr et al, 2015). Therefore, we determined the effect of TAX to the cardiac function parameters of isolated heart in myocardial I/R injury by using the Langendorff equipment.…”
Section: Discussionmentioning
confidence: 99%
“…At the first stage, a total of 48 rats were divided into six groups (n=8 per group), to determine the best concentration of SA treatment as follows. (I) Control group: The isolated heart continuously perfused with Krebs-Henseleit (K-H) solution (in mM: 112 NaCl, 5 KCl, 1.2 MgSO 4 , 1 K 2 HPO 4 , 1.25 CaCl 2 , 25 NaHCO 3 , 11 D-glucose, 0.2 octanoic acid, pH=7.4) 17 for 150 min without ischemia. (II) Ischemia reperfusion (IR) group: The isolated heart underwent 30-min ischemia, followed by 120-min reperfusion.…”
Section: Experiments Groupsmentioning
confidence: 99%